Right to food information and food choice from the perspective of fundamental liberties / Nor Akhmal Hasmin, Najwa Azizun and Siti Marina Amit - Hasmin, Nor Akhmal; Azizun, Najwa; Amit, Siti Marina (Universiti Teknologi MARA Cawangan Pulau Pinang, 2022)
The Federal Constitution is silent on protecting consumers' right to food information and choice. The food label is a source of information and a tool to assist consumers in making food choices. In certain situations, information available on the product's label is limited, restraining consumers from making well-inform food choices, especially concerning credence food products derived from emerging technology such as nanotechnology. Such food is also associated with potential safety and health risks. This paper aims to explore the right to food information and choice from the perspective of the fundamental liberties embodied in the Federal Constitutions, i. e., the right to life and freedom of speech and expression. It adopts a doctrinal approach and content analysis by examining relevant literature on consumer rights to food information, food choice, and fundamental liberties. The finding from this paper indicates that the right to food information and food choice is implicitly part of fundamental liberties in the Federal Constitution. Food choice is associated with consumers' quality of life and their expression of religious beliefs, personal values, and identity. Therefore, consumers must be given the right to be directly involved in labelling issues, i.e., to demand necessary information, which is pivotal to food choices. Reference is made to the legal position under the Universal Declaration of Human Rights (UDHR), Constitution of India and the European Union. This article is intended for the food safety authority and the public because, to date, awareness of constitutional rights in Malaysia's food information law and food labelling is still absent.